2018
DOI: 10.2217/imt-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Positive Efficacy Results after Subcutaneous Immunotherapy with Parietaria Judaica Depot Extract

Abstract: Aim: To evaluate tolerability and efficacy of Parietaria judaica subcutaneous immunotherapy on patients with allergic rhinoconjunctivitis. Patients & methods: 51 patients were assigned to build-up scheme (six increasing doses) of P. judaica depot native extract, plus three maintenance monthly administrations. Results: Out of 470 administered doses, only 3.8% elicited systemic reactions (1.5% nonspecific and 2.3% grade I). Concerning the exploratory efficacy parameters: cutaneous reactivity at the final vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Another interesting aspect is the tolerability of SCIT: a very recent study demonstrated that Parietaria judaica subcutaneous immunotherapy (Allergovac ® depot ROXALL Medicina España), with an abbreviated up-dosing scheme, showed an adequate safety and tolerability profile and induced preliminary efficacy changes [53]. This indicates that a rapid schedule may be safe and well tolerated.…”
Section: Allergen Immunotherapy For Parietaria Allergymentioning
confidence: 99%
“…Another interesting aspect is the tolerability of SCIT: a very recent study demonstrated that Parietaria judaica subcutaneous immunotherapy (Allergovac ® depot ROXALL Medicina España), with an abbreviated up-dosing scheme, showed an adequate safety and tolerability profile and induced preliminary efficacy changes [53]. This indicates that a rapid schedule may be safe and well tolerated.…”
Section: Allergen Immunotherapy For Parietaria Allergymentioning
confidence: 99%